The Effect Of Work Stress And Work Motivation On The Performance Of Civil Servants At The Cikarang Health Training Center, Ministry Of Health, Republic Of Indonesia - Sumarno, Sumarno; Rindu, Rindu; Atiq Amanah Retna Palupi (Sean Institute, 2024)
Since the onset of the COVID-19 pandemic, the public service sector has faced significantly increasing work demands. Government agencies, including the Cikarang Health Training Center under the Ministry of Health of the Republic of Indonesia, have been challenged to meet higher performance targets without a proportional increase in staff or rapid technological adaptation. This situation has led to heightened levels of work stress among civil servants, potentially affecting their motivation and overall performance. In this complex era, managing work stress and motivating employees have become crucial to maintaining productivity and performance in government institutions. This study applied a quantitative approach by distributing questionnaires to 55 civil servants at the Cikarang Health Training Center who met the inclusion criteria. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The findings show that work motivation has a positive and significant impact on performance (path coefficient = 0.712, p-value < 0.05), and work stress also significantly affects performance (path coefficient = 0.243, p-value < 0.05). Furthermore, work stress positively affects motivation (path coefficient = 0.677, p-value < 0.05), with motivation mediating the relationship between work stress and performance. This suggests that work stress, when managed effectively, can improve performance through increased motivation. The study concludes that stress management and work motivation enhancement programs should be implemented at the Cikarang Health Training Center to optimize civil servant performance.